Evaluation of Development of Renewable Energy Sources for Different Power Generation System - Rahul Deepke (Journal of Power Electronics and Devices, 2020)
Energy is the primary and most universal life of all types of labor by men and nature. The energy consumption is directly proportional to the progress of man. With an ever-increasing population, manufacture of the developing countries, recent trends, and developments in varied technologies/rapid technological enhancements, the worldwide energy demand is anticipated to extend rather considerably within the close to future. the first supply of energy is fuel, but thanks to the restricted offer of fossil fuels and huge scale environmental degradation caused by their widespread use, significantly warming, environmental pollution, and air pollution, powerfully suggests that harnessing of non-conventional, renewable, and environmental eco-friendly energy sources is important for steering the worldwide energy provides towards a property path. This paper describes, in short, the non-conventional energy sources and their importance for developing countries.